Pemanfaatan Limbah Talas Pratama (Colocasia esculenta) Menjadi Pelet Ikan: Peluang Nilai Tambah dan Dampaknya bagi Kesejahteraan Petani - Heryadi, D. Yadi; Rofatin, Betty; Pebrianti, Suci Apsari; Nurcahya, Intan; Yuliyani, Leny (Universitas Galuh, 2026)
Talas Pratama (Colocasia esculenta) is one of the promising local food crops that has recently gained popularity due to its high productivity, reaching 7–8 kg of tubers per plant at eight months of age. Alongside tuber production, this crop generates substantial agricultural waste in the form of petioles, stems, and leaves. At present, these by-products are commonly used as vegetables or as supplementary feed for fish. However, to enhance their economic value, such biomass needs to be processed into fish feed in the form of pellets, thereby creating added value that can potentially increase farmers’ income. The specific objectives of this study are to determine the value addition obtained from processing Talas Pratama waste into fish pellets and to calculate the profitability for small-scale entrepreneurs. In the long term, this research contributes to the development of an agribusiness model for local food commodities in line with the researcher’s established roadmap. The study employed a case study approach with a Talas Pratama farmer in Gunajaya Village, Manonjaya District, Tasikmalaya Regency, West Java. Both primary and secondary data were collected and analyzed using descriptive statistics and value-added analysis based on the Hayami method. The results of the study showed that processing Pratama Taro waste into fish pellets had an added value of Rp6.400,00/kg. and the profit obtained by entrepreneurs was Rp2.400,00/kg.